Dermatomycoses Among People Living with Diabetes Mellitus in Kano, Nigeria - Amina Idris; Taysir Ramadan; Kabuga Auwal; Azeez Akande; Lawal Rogo; Muhammad Abbas; Alhassan Abdullahi; Mustapha Yusuf; Abdulsalami Manu; Almukhtar Adamu; et al. (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Dermatomycoses can cause debilitating effects on a person’s quality of life, or become invasive in immuno-compromised individuals such as People Living with Diabetes Mellitus (PLWDM). PLWDM are highly susceptible to various kinds of dermatomycoses because of their immunocompromised state, autonomic neuropathy, impaired peripheral circulation and inability to maintain good foot hygiene due to obesity, impaired vision or advanced age. Dermatomycoses can in turn, result in diabetic foot, and together with their attending sequelae result in prolonged hospital stay, increasing risks of amputations, other associated morbidities and mortality. Thus, this study aimed to detect and identify the fungal pathogens associated with dermatomycoses among PLWDM attending some diabetic clinics in Kano. Methods. Three hundred (300) diabetic individuals with superficial lesions were selected and enrolled. Socio-demographic data, medical history and other risk factors of dermatomycoses were also assessed and analysed. Skin scrapings, nail clippings and swabs from foot ulcers were collected and cultured on Sabouraud Dextrose Agar (SDA). Identification of yeasts and moulds isolates was done using Gram stain, germ tube test, Chrom agar, lactophenol cotton blue mount and slide cultures. Results. The prevalence of fungal pathogens detected from various lesions was 28.3%. The spectrum of fungal pathogens isolated includes; dermatophytes, yeasts and non-dermatophytes moulds. Trichophyton mentagrophytes, Trichophyton rubrum, Epidermophyton floccosum, Candida albicans, Candida tropicalis, Candida glabrata, Aspergillus species and Fusarium spp were the predominant isolates recovered. Poor glycaemic control, prolonged duration of DM, use of oral antidiabetic drugs and exposure to domestic animals were some of the risk factors identified. Conclusion. the study shows high prevalence of superficial mycoses in a cohort of People Living with Diabetes Mellitus studied in Kano, and therefore calls for routine screening and prompt institution of appropriate management in order to minimize or eliminate all possible complications.